PENGARUH PENGAWASAN, DISIPLIN KERJA, KOMUNIKASI DAN PEMBERDAYAAN TERHADAP SEMANGAT KERJA PEGAWAI UNIVERSITAS KARIMUN - Waidah, Dina Fara (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2019)
Analysis that is done on result observationaling to cover observational instrument examination, analyse bifilar linier regression, claassic assuming quiz, and hypthosts testing. Bifilar linier regression count result f computing as big as 26.625 f table as big as 2.51 by df counter 4 and denominator 55.Thus therefore evident that f computing are event greater that f table that Ho's matter is refused and accepts Ha on increases signifikan as big as 0.000. Its mean that exizts influence that signifikan variables observation, job discipline, coommunication, and empowerment together ala (simultan) to is ardour job. That partially exhaussstive variable free one consisting of observation, job discipline, communicstion, and empowerment having for partially to bonded variable (job spirit). Variable that have dominant influence is variable empowerment (X4) with point t computing as big as 3.445 greatter as compared to point t computungs for variable another one.